2013
DOI: 10.1016/j.epsl.2013.06.044
|View full text |Cite
|
Sign up to set email alerts
|

Coulomb stress evolution along Xianshuihe–Xiaojiang Fault System since 1713 and its interaction with Wenchuan earthquake, May 12, 2008

Abstract: The curved left-lateral strike-slip Xianshuihe-Xiaojiang fault system (XXFS) in southwestern China extends at least 1400 km in the eastern margin of the Tibetan Plateau. Fieldworks confirm that the XXFS is one of the longest and most seismically active faults in China. The strain released by the slip motion on the XXFS is related to the convergence between the Indian and Eurasian plates. The entire fault system has experienced at least 35 earthquakes of M>6 in the recent 300 years and almost all segments of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 64 publications
6
63
0
Order By: Relevance
“…We calculate the Coulomb stress changes on faults using a range of effective friction coefficients from 0 to 0.8 and find that the general pattern of Coulomb stress changes does not change with the different effective friction coefficients. Hence, we show in most cases the results using an effective friction coefficient of 0.4, which is the commonly used value in studies of Coulomb stress changes (e.g., Freed et al, ; King et al, ; Luo & Liu, ; Shan et al, ). The results show that the Coulomb stress on northern and central Longmenshan fault, where the 2008 M w 7.9 Wenchuan earthquake occurred, was reduced by the preceding earthquakes on the Xianshuihe, Anninghe, and Zemuhe faults and the 1933 M 7.5 Diexi earthquake on the nearby Minjiang fault (Figures a and b).…”
Section: Results and Analysismentioning
confidence: 78%
See 1 more Smart Citation
“…We calculate the Coulomb stress changes on faults using a range of effective friction coefficients from 0 to 0.8 and find that the general pattern of Coulomb stress changes does not change with the different effective friction coefficients. Hence, we show in most cases the results using an effective friction coefficient of 0.4, which is the commonly used value in studies of Coulomb stress changes (e.g., Freed et al, ; King et al, ; Luo & Liu, ; Shan et al, ). The results show that the Coulomb stress on northern and central Longmenshan fault, where the 2008 M w 7.9 Wenchuan earthquake occurred, was reduced by the preceding earthquakes on the Xianshuihe, Anninghe, and Zemuhe faults and the 1933 M 7.5 Diexi earthquake on the nearby Minjiang fault (Figures a and b).…”
Section: Results and Analysismentioning
confidence: 78%
“…However, estimating stressing rates on these faults is challenging. Some studies apply the deep‐slip or back‐slip models constrained by Global Positioning System (GPS) data to calculate stressing rates on faults (Loveless & Meade, ; Shan et al, ; Smith & Sandwell, ), but these studies have to assume a lithospheric deformation mechanism and rheology. Other studies directly use GPS data to calculate strain rates and apply the results to estimate stressing rates on faults by elastic Hooke's law (Freed et al, ; Jiang et al, ; Wang, Liu, et al, ; Wang, Wang, et al, ), but the GPS sites are usually sparse near fault zones and the near‐fault strain rates need to be extrapolated, leading to large uncertainty on the resulting stressing rates.…”
Section: Introductionmentioning
confidence: 99%
“…Third, high strain rates occur along the whole Xianshuihe‐Xiaojiang fault system, where previous studies have identified four seismic gaps (Shan et al, ; Wen et al, ). The recent 2014 M w 5.9 Kangding earthquake struck the Kangding‐Daofu gap; however, the released strain energy was far less than that accumulated (Jiang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The numerical results indicate that the amplitudes of ΔCFS vary depending on the different friction coefficients, but the spatial distribution patterns of Coulomb stress changes are highly consistent (Additional file 1: Figure S5). Therefore, we considered an empirical and moderate effective coefficient of friction of 0.4 (Shan et al 2013a, b;Xiong et al 2010Xiong et al , 2017 for our ΔCFS calculation and discussion.…”
Section: Coseismic Coulomb Stress Changes In Mainshock Rupture Regionmentioning
confidence: 99%
“…The Coulomb failure criterion describes the fracture behavior of rock considering both shear and normal stress changes on a predefined surface (King et al 1994;Liu et al 2017;Shan et al 2013a;Stein 2000): where ΔCFS is the Coulomb failure stress (CFS) change; Δτ s and Δσ n are the shear stress and normal stress changes on the receiver fault, respectively; and µ ′ is the equivalent friction coefficient. Based on the seismic stress triggering theory, positive (increased) CFS change causes regional faults to be closer to failure and leads to seismic activity, whereas faults in stress shadow areas are further away from failure, reducing the possibility of seismicity (Freed 2005;Shan et al 2015).…”
Section: Coseismic Coulomb Stress Changes In Mainshock Rupture Regionmentioning
confidence: 99%